La afectación de la independencia judicial en México tras la reforma constitucional de 2024: una reflexión jurídico-constitucional - Martín Guardado, Sergio (Pontificia Universidad Católica del Perú, 2025)
The constitutional reform of the Judiciary in Mexico, enacted in 2024, represents an unprecedented structural change that seriously affects the principle of judicial independence, a cornerstone of the rule of law and constitutional democracy. This reform introduces the popular election of judges, magistrates, and Supreme Court justices; eliminates the Federal Judiciary Council; restructures the Supreme Court; and alters the rules of access, tenure, and judicial discipline itself. Under the guise of enhancing the democratic legitimacy of justice, the reform weakens the principles of impartiality, professionalism, and separation of powers, placing the judge within a logic of political representation that is foreign to the nature of the judicial function. This article analyzes the effects of this institutional transformation from a dogmatic legal perspective, arguing that the new model breaks with the counter-majoritarian logic that must prevail within the judiciary by seeking to align and subordinate it to political cycles and electoral contingencies.

La reforma constitucional al Poder Judicial en México, promulgada en 2024, representa un cambio estructural sin precedentes que impacta gravemente el principio de independencia judicial, piedra angular del Estado de Derecho y de la democracia constitucional. Esta reforma introduce la elección popular de jueces, magistrados y ministros, elimina el Consejo de la Judicatura Federal, reestructura la Suprema Corte de Justicia de la Nación y altera las reglas de acceso, permanencia y la misma disciplina judicial. Bajo la apariencia de ampliar la legitimidad democrática de la justicia, la reforma debilita los principios de imparcialidad, profesionalismo y separación de poderes, colocando al juez en una lógica de representación política ajena a su función jurisdiccional. El presente artículo analiza los efectos de esta transformación institucional desde una óptica dogmática, donde se advierte que el nuevo modelo rompe con la lógica contra mayoritaria que debe regir en el seno del Poder Judicial, al pretender alinearlo y someterlo a ciclos políticos y coyunturas electorales.
The impact on judicial independence in Mexico after the 2024 constitutional reform: a legal-constitutional reflection
Keywords: Judicial power; Independence of justice; Popular election; Politicization of justice; Rule of law; Separation of powers; Poder Judicial; Independencia de la justicia; Elección popular; Politización de la justicia; Estado de derecho; Separación de poderes; https://purl.org/pe-repo/ocde/ford#5.05.01